2009
DOI: 10.1007/s10695-009-9310-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and differentiation of sea trout (Salmo trutta) populations in Lithuanian rivers assessed by microsatellite DNA variation

Abstract: The genetic diversity and differentiation of sea trout were studied in three river basins in Lithuania: Akmena-Dane, Bartuva, and Nemunas. A total of 282 individuals were genotyped at eight microsatellite loci. A similar level of genetic diversity was found in all of the populations studied: mean allelic richness ranged from 3.64 to 5.03, and average expected heterozygosity ranged from 0.588 to 0.721. Significant genetic divergence was observed among the different river basins as well as between populations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…This is congruent with other studies of sea trout where IBD has been observed (Moran et al 1995;Hansen & Mensberg 1998;Samuiloviene et al 2009) and also the nonexistence of IBD among samples of resident brown trout (Ryman 1983;Carlsson & Nilsson 2001). This is congruent with other studies of sea trout where IBD has been observed (Moran et al 1995;Hansen & Mensberg 1998;Samuiloviene et al 2009) and also the nonexistence of IBD among samples of resident brown trout (Ryman 1983;Carlsson & Nilsson 2001).…”
Section: Genetic Structuresupporting
confidence: 91%
See 1 more Smart Citation
“…This is congruent with other studies of sea trout where IBD has been observed (Moran et al 1995;Hansen & Mensberg 1998;Samuiloviene et al 2009) and also the nonexistence of IBD among samples of resident brown trout (Ryman 1983;Carlsson & Nilsson 2001). This is congruent with other studies of sea trout where IBD has been observed (Moran et al 1995;Hansen & Mensberg 1998;Samuiloviene et al 2009) and also the nonexistence of IBD among samples of resident brown trout (Ryman 1983;Carlsson & Nilsson 2001).…”
Section: Genetic Structuresupporting
confidence: 91%
“…The structuring is similar to other studies of brown trout genetic structure on similar geographical scales (Hansen et al 2002;Lehtonen et al 2009;Massa-Gallucci et al 2010;Samuiloviene et al 2009). The structuring is similar to other studies of brown trout genetic structure on similar geographical scales (Hansen et al 2002;Lehtonen et al 2009;Massa-Gallucci et al 2010;Samuiloviene et al 2009).…”
Section: Genetic Structuresupporting
confidence: 89%
“…European, and especially Baltic, sea trout populations have been frequently studied mainly of Danish and Swedish stocks (i.e. Hansen & Mensberg 1998;Laikre et al 2002;Fraser et al 2007;€ Ostergren et al 2011), but also Polish (Was & Wenne 2002Drywa et al 2013), Lithuanian (Samuiloviene et al 2009) and Russian (Lehtonen et al 2009) stocks. However, works focused on population structure from a single basin are rarer and absent in southern Baltic rivers.…”
Section: Introductionmentioning
confidence: 99%
“…Also, according to the expected and observed heterozygoty values, it is clearly seen from the graph that the interpopulation genetic distance is the farthest in FRT population. Samuiloviene et al (2009) reported that significant population differentiation was found both between river systems and between population pairs within the same river system in sea trout (Salmo trutta) populations in Lithuanian rivers. They suggested that even geographically adjacent tributaries exhibited significant genetic differences.…”
Section: Resultsmentioning
confidence: 99%